Erenumab efficacy predictors for chronic migraine - Nina V. Vashchenko (ZAO "Consilium Medicum", 2022)
The diagnosis of chronic migraine (CM) is made when there are 15 or more days of headache per month in a patient with migraine. Approximately 2.5% of patients with episodic migraine develop chronic migraine, which is more difficult to treat and often leads to drug-induced headache (LIH). Such patients are rarely included in clinical trials. Aim. To analyze in clinical practice the effectiveness of the CGRP monoclonal antibody erenumab after 6 months of therapy in patients with CM with and without LIHD, and to evaluate possible predictors of the effectiveness of prophylactic therapy. Materials and methods. The study included 47 patients with CM taking erenumab at a dose of 70 mg monthly for at least 3 months. Patients completed a headache diary throughout the study. The 12-item Allodynia Symptom Checklist (ACS-12) was used to assess the presence of allodynia. After 6 months of therapy, the efficacy and safety of treatment, the presence of LAH and possible predictors of efficacy were evaluated. Results. After 6 months of therapy, 22 (78.6%) patients no longer met the criteria for LIHD. The factors that positively influenced the outcome of therapy were the absence of allodynia (p0.05), the presence of photo- and phonophobia, and the one-sidedness of pain (p0.05). The age and number of days with headache in patients with HM before treatment did not have a statistically significant effect on the effect of therapy. The presence of LIHD did not statistically significantly affect the outcome of therapy. Conclusion. CGRP monoclonal antibodies are reasonable in patients with LIHD. The presence of LIHD does not affect the efficacy of erenumab prophylactic therapy, the presence of allodynia may be a predictor of failure, and the unilaterality of pain and irritability to light and sound indicate likely efficacy. Real-world studies with a large cohort of patients and longer durations of therapy are required to confirm these results.